Efforts to Improve Soccer Passing and Stopping Skills Through Audiovisual Media Among Students at SMPN 12 Pekanbaru in the 2024/2025 Academic Year - Pratama, Yudistira; Apriani, Leni (Indonesian Journal of Sport Management, 2025)
Physical education is an important part of the educational process that focuses not only on physical fitness, but also on the psychological, social, and motor skill development of students. One of the sports that is widely taught in physical education is soccer, where mastery of basic techniques such as passing and stopping are fundamental skills that students must master. However, in reality, many students experience difficulties in mastering these two techniques, thus requiring innovation in the learning process. This study aims to improve students' passing and stopping skills through the use of audio-visual learning media. The research method used was Classroom Action Research (CAR) with two cycles involving 23 students of class VII.3 SMPN 12 Pekanbaru, consisting of 13 male students and 10 female students. Each cycle was carried out through the stages of planning, action, observation, and reflection using learning tools such as lesson plans, observation sheets, and soccer skill assessment instruments. The results of the study showed a significant increase in students' passing and stopping skills, with learning completeness increasing from 52.78% in cycle I to 82.60% in cycle II. The conclusion of this study confirms that the use of audio-visual media can be an effective alternative learning strategy in improving the mastery of basic soccer techniques. The implication of this study is the need for physical education teachers to integrate audio-visual media more intensively so that learning becomes more interesting, interactive, and able to improve student learning outcomes.